Виховна робота у ВНЗ як чинник формування особистості майбутнього фахівця - Дурманенко, Оксана; Durmanenko, O. (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті подається сутність, структура, функції та етапи організації виховної роботи у вищому навчальному закладі як одного із важливих чинників формування особистості майбутнього фахівця; конкретизовано мету та завдання виховної роботи у вищому навчальному закладі; проаналізовано управлінський аспект в організації виховної роботи. The article deals with the concept of essence, the structure, functions and stages of extracurricular activities in higher school as one of the important factors of forming future specialist personality. The aim is specified and the main tasks of extracurricular activities in higher schools are analyzed. The administrative aspect of extracurricular activities and the role of the teacher in providing subject-subject interaction between teachers and students in higher school are revealed.
Extracurricular activity in higher school as a factor of forming future specialist personallity
Keywords: особистість; personality; майбутній фахівець; виховна робота; завдання виховної роботи; вищий навчальний заклад; the future specialist; extracurricular activity; the tasks of extracurricular activities; Higher school